Taxonomy on Quedius euryalus group (Coleoptera: Staphylinidae: Staphylinini: Quediina) from China with description of eight new species - Cai, Yan-Peng; Zhao, Zong-Yi; Zhou, Hong-Zhang (Zootaxa, 2015)
Eight new species of the subgenus Microsaurus Dejean, 1833 of the genus Quedius Stephens, 1829 are described based on specimens collected in China, namely Q. aculeatus sp. nov., Q. acutulus sp. nov., Q. altus sp. nov., Q. capillus sp. nov., Q. perlucidus sp. nov., Q. postangulus sp. nov., Q. subwrasei sp. nov. from Sichuan and Q. arcus sp. nov. from Ningxia. The female of Q. songpanoides Smetana, 2009 is described for the first time. These new species belong to the Quedius euryalus group and the fauna of this species group is thus increased to 53 species. In addition, this paper reviews the taxonomic history of the Quedius euryalus group and reports the sexual dimorphism in the hind wing length, i.e. male with longer hind wings in many species of the Quedius euryalus group. Line drawings and color illustrations of adults and genitalia of the new species and some other ones are provided, along with a key to all the known species of the euryalus group.